Soil and geological considerationm for the sitting of a sanitary landfill. - Sapari, Nasiman (1981)
Landfill impact on the surrounding surface and groundwater depends on the soil and the geological conditions of the site. Many rock types are owrvious in nature, especially if they are fractured and jointed. Leachats from a disposal ground may travel through the pwervious rocks and cause water pollution. This problem can be overcome bt sealing the rocks with an impervious layer of clay. Soils a cover materials are generally classified according to their textture. Finr grained materials are suitable to be used for prevention of gas and leachate movement. Coarse grained materials can be used for venting gas. Abandoned depressions are the commonly available land for landfill sites. Ravine, canyons and stone quarries require site improvementbefore they can be used as waste disposal grounds. Depression on limestone formations are not suitable for landfills. Pollution from a landfill using these depressionis almost impossible to be controlled. Clay pits are the best sites for sanitay landfills.